The Pragmatic perspective in Iben Djinni’s book ‘El khassais’ - Benmicia, Rafika (Journal of Human Sciences, 2020)
This study aims at  demonstrating  some of The Pragmatic perspective in  Iben Djinni’s book ‘El khassais’. These perspective are considered  to be outstanding  ideas for the ancient Arabic course of the language and also a solid base for the modern and  contemporary course of pragmatics. Those notions consist of the elements of the communicative  process, the function of the language, the relationship between the function and the structure, and  the linguistic  competence  and the communicative competence . Thus, it is obvious that the modern and the contemporary  occident  course of the language is just an extension of the ancient Arabic one, and there is no Epistemological  rupture between them  despite of the differences in the methods of presentation of the ideas, the methodology of the analysis and the purpose from the study.